Riding the Wave of Change: Unmasking Transformative Shifts in Digital Activism for Social Justice in Indonesia - Rizky Bangun Wibisono; Sultoni Fikri (Mimbar Keadilan, 2024)
This research delves into the transformative shifts in social media use in Indonesia, exploring how it has become more than a personal necessity, evolving into a powerful tool for civic engagement and justice advocacy. Focusing on the "No Viral, No Justice" movement, we dissect its impact on the nation's digital landscape and law enforcement dynamics. The analysis reveals a complex interplay of positive change and potential pitfalls, including the risk of echo chambers. The study emphasizes the significance of digital activism, transcending its role as a mere trend, and underscores its importance in holding authorities accountable. The narrative navigates through real-life examples, such as the case of sexual harassment at the Indonesian Broadcasting Commission, illustrating how social media acts as a catalyst for justice. The reflection section addresses the looming threats associated with this evolving trend and proposes strategies for mitigation. This research contributes to understanding the nuanced role of social media in Indonesian society, shedding light on both its transformative potential and the imperative need for responsible digital activism.